The ISIS reader: milestone texts of the Islamic State movement - Ingram, Haroro J. (Hurst & Company, 2020)
In the wake of its 'Caliphate' declaration in 2014, the self-described Islamic State has been the focus of countless academic papers, government studies, media commentaries and documentaries. Despite all this attention, persistent myths continue to shape - and misdirect - public understanding and strategic policy decisions. A significant factor in this trend has been a strong disinclination to engage critically with Islamic State's speeches and writings - as if doing so reflects empathy with the movement's goals or, even more absurdly, may itself lead to radicalisation. Going beyond the descriptive and the sensationalist, this volume presents and analyses a series of milestone Islamic State primary source materials. Scholar-practitioners with field experience in confronting the movement explore and contextualise Islamic State’s approach to warfare, propaganda, leadership, and governance. Telling the 'inside story' of the Islamic State movement, they examine the factors behind its dramatic evolution from a wandering 'band of brothers' led by Abu Musab al-Zarqawi to Islamic State in Iraq then failed proto-state by 2010, standard-bearer of global jihadism in 2014 to besieged insurgency in 2019.